2016
DOI: 10.15312/eurasianjvetsci.2016318398
|View full text |Cite
|
Sign up to set email alerts
|

Detection of methicilline resistant Staphylococcus aureus carrying mecC gene in mastitic milk samples of cattle in Turkey

Abstract: Öz Amaç: Mastitisli ineklerin süt örneklerinden izole edilen ve fenotipik olarak metisilin dirençli Staphylococcus aureus (MRSA) olduğu belirlenen izolatlarda, mecC gen varlığının araştırılması amaçlandı. Gereç ve Yöntem: Çalışma materyalini mastitisli ineklerden izole edilen 150 adet Staphylococcus aureus (S. aureus) suşu oluşturdu. İzolatlardaki metisilin direnci sefoksitin disk difüzyon testi ve ticari PBP2a lateks aglütinasyon testi ile belirlendi. MRSA izolatlarında mecA ve mecC gen varlığı Polimeraz Zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…Researchers from several countries have reported the rate of MRSA in milk as 50%, 13%, 9.7%, 4.4%, 2.5%, and 0.7% (Kreausukon et al, 2012;Jamali et al, 2015;Parisi et al, 2016;Giacinti et al, 2017;Asiimwe et al, 2017;Tenhagen et al, 2018). Previous studies from Turkey have indicated lower rates than the current study: Ektik et al (2017) 14.28%, Sayin et al (2016) 18.6%, Siiriken et al (2016) 13.3% and Buyukcangaz et al (2013) 15.8%. By contrast, Can et al (2017b) reported the rate of MRSA to be much higher at 90%.…”
Section: Discussioncontrasting
confidence: 50%
“…Researchers from several countries have reported the rate of MRSA in milk as 50%, 13%, 9.7%, 4.4%, 2.5%, and 0.7% (Kreausukon et al, 2012;Jamali et al, 2015;Parisi et al, 2016;Giacinti et al, 2017;Asiimwe et al, 2017;Tenhagen et al, 2018). Previous studies from Turkey have indicated lower rates than the current study: Ektik et al (2017) 14.28%, Sayin et al (2016) 18.6%, Siiriken et al (2016) 13.3% and Buyukcangaz et al (2013) 15.8%. By contrast, Can et al (2017b) reported the rate of MRSA to be much higher at 90%.…”
Section: Discussioncontrasting
confidence: 50%